Gratitude Training: Improving Life Expectancy for People with Chronic Diseases - Syaiful, Irfan Aulia; Fadhiilah, Nabiilah; Arafah, Rizanita Zulfa; Sriyanto, Arie Suciyana; Atika, Atika (Psikis : Jurnal Psikologi Islami, 2024)
People suffering from chronic diseases such as breast cancer and heart disease usually feel they have low life expectancy. Gratitude skills considered to be one of factors that could increase the hope for life and promoting the recovery of patients with chronic diseases. To prove this assumption, research was conducted to prove whether gratitude training could increase hope for life in adult patients with breast cancer and heart diseases. This research used a quasi-experimental method randomized two groups (control and experiment) pretest-posttest design, following the gratitude research procedures conducted by Bahar & Moordiningsih on heart disease in 2020. This research involved 32 (21 females, 11 males) with the age range from 30 to 61 years old (Mean = 49.50, SD = 8,474). Participants in this study were divided into two groups consisting of 14 participants in the experimental group (7 with breast cancer, 7 with heart disease) and 18 participants in the control group (9 with breast cancer, 9 with heart disease). The research results showed gratitude training is effective in improving hope for life. The findings also revealed that participants with heart disease experienced a higher effect of gratitude training than participants with breast cancer.